FUNDING AND PRIORITIES: ACADEMIC LIBRARIES THE LIBRARY RESOURCE GUIDE BENCHMARK STUDY ON 2011 LIBRARY SPENDING PLANS - McKendrick, Joseph (Unispear Research, 2011)
Academic libraries—typically shielded from economic disturbances by the institutions they serve—have not been immune to the double-barreled crisis sweeping the library world. Many academic libraries are running on tight budgets that keep getting tighter, and, as is the case with libraries across the spectrum, they are contemplating their future in the digital age. While the recent economic pinch has bottomed out, and some academic libraries anticipate upticks in their budgets, many are stepping up their efforts to share or deliver knowledge digitally. These are some of the conclusions of a recent survey of 470 academic library managers and professionals from across North America. This study, conducted by the Library Resource Guide (LRG)—in conjunction with Unisphere Research, the market research division of Information Today, Inc. (ITI)—in October and November 2010 among libraries listed in ITI’s American Library Directory, reveals current spending patterns for public, academic, government, and special libraries, and projects budget and other spending trends for 2011. A total of 1,201 libraries representing four key segments—academic libraries, public libraries, special and corporate libraries, and government (mainly state, federal and armed forces) libraries—responded to the survey. In this survey, 79% of the academic libraries surveyed are four-year or graduate-level college or university libraries, and another 21% are affiliated with community colleges, two-year colleges, or technical schools. Among the 470 respondents are directors, administrators, managers, department heads, and librarians from the complete range of library settings and sizes. One-fourth serve populations of greater than 10,000 constituents, and another 16% serve between 5,000 and 10,000 people. More than one-third of respondents service campuses with fewer than 2,500 people. (For detailed demographic breakdowns, see Figures 29–34 at the end of this report.) Key findings from the survey include the following: While the past year has been difficult for many academic libraries financially, prospects are brighter for the year ahead. Larger academic libraries suffered the most severe cuts, while fewer cuts were seen among the smallest libraries, which already operate on relatively little funding. Next year, while larger institutions anticipate more rounds of cutbacks, relatively few small college libraries will be paring their budgets. Typical annual budgets currently fall in the range of $1.2 million to just above $3 million, and the largest portion of that funding goes to staffing. Four out of five academic libraries have cut back in one or more areas over the past year, led by cuts in subscriptions and staff training. Larger academic libraries are also putting more pressure on vendors to renegotiate contracts for more favorable terms. Print resources still consume a majority of annual content budgets, but almost all growth in demand among academic libraries is for digital information and technology resources. Academic libraries maintained their information technology system budgets through the budget storm, and are growing their online subscription purchasing. One-third of academic libraries are also subscribing to, or considering use of, public cloud computing resources, particularly online communication and collaboration tools. Social media tools are also now part of most academic libraries’ offerings. From a strategic perspective, most academic libraries see the future as digital, and are directing efforts to increase accessibility and awareness of digital offerings. One important challenge for academic libraries—which separates them from other library segments—is that they serve members of “Generation Y” (those born between 1980 and 2000), a group that grew up looking to the web and internet for their information needs. As one respondent, a department head of a small college library, put it, “Our future patrons are savvy in the use of technology. The big challenge is being able to foresee their preferences, and make sure that administrators— especially those in academia—recognize and value the importance and relevance that knowledge and information access has today.” Another respondent, a department head of a large Texasbased university library, echoes this sentiment, stating that academic libraries need to be able to support an emerging online generation. “The single biggest challenge facing libraries is staying relevant to a much more technologically advanced and sophisticated patron base,” she says. “We need to be ready to deploy library services at a moment’s notice to whatever venue the patrons utilize for communication and information discovery.” This is the challenge of the 2010s decade and, as this survey shows, many academic libraries are responding with new initiatives in technology access, online subscriptions, and cloud computing. However, financial support is always an issue.
Funding and Priorities: The Library Resource Guide Benchmark Study on 2011 Library Spending Plans was produced by Unisphere Research and sponsored by ProQuest. Unisphere Research is the market research unit of Unisphere Media, a division of Information Today, Inc., publishers of Database Trends and Applications magazine and the 5 Minute Briefing newsletters. Unisphere Media, 229 Main Street, Chatham, NJ 07928. Tel: 973-665-1120, Fax: 973-665-1124, Email: Tom@dbta.com, Web: www.dbta.com. Data collection and analysis performed with SurveyMethods. © Copyright 2011, Information Today, Inc. All rights reserved
Keywords: Academic Libraries; Electronic Resources; Demographics; Library Resource Guide